Penerapan Strategi Modeling untuk Mengembangkan Perilaku Disiplin pada Anak Prasekolah - Raudatul Hasanah; Nor Fatmah (Institut Agama Islam Negeri Padangsidimpuan, 2026)
Abstract Discipline is one of the important foundations that should be introduced to children during the preschool years because it helps them build habits, follow routines, and learn responsibility in everyday activities. In reality, some children still find it difficult to follow classroom rules, complete simple tasks independently, or maintain orderly behavior during learning activities. This study aims to explore how modeling strategies are applied in developing disciplined behavior among preschool children. The research used a descriptive qualitative approach involving preschool children and teachers who actively participated in classroom activities. Data were obtained through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that children tend to learn discipline more easily when they directly observe consistent examples from teachers and their surrounding environment. Behaviors such as putting toys back in place, queuing patiently, and following classroom schedules gradually became part of children’s daily routines through observation and repetition. Positive responses, encouragement, and supportive interactions also strengthened the development of disciplined behavior. The study shows that modeling strategies can help preschool children understand and practice discipline naturally through meaningful daily experiences in the learning environment. Keywords: discipline, modeling strategy, preschool children, observational learning, early childhood education